ANALISIS MODEL PROSES INKREMENTAL DALAM PERANCANGAN SISTEM INFORMASI GEOGRAFIS BERBASIS WEB - Faisal - (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2013)
Nowadays, the web based GIS exploiting beginning to start developing for many application. One among them is web based GIS development in land area in the form of land information system. This research aim to develop a web based GIS, especially land information system, by analysis of incremental process modelling as one of software engineering models. The development of the GIS is using tolls like ArcView, Adobe Photoshop, Macromedia Dreamweaver, Apache and MySQL. The result of this research showed that the analysis of incremental process model in web based GIS.